Adjustable electrical characteristics in hybrid Si/PEDOT:PSS core/shell nanowire hetero-junctions. Issue 16 (6th April 2017) - Lu, Wenhui; Zhang, Shuai; Dai, Enqi; Miao, Bin; Peng, Yiran; Pang, Tao; Zhang, Tiansheng; Yan, Lei; Zhang, Shuxin; Li, Jiadong; Wang, Xingzhu
Abstract : Si/PEDOT:PSS core/shell nanowire hetero-junctions with adjustable electrical characteristics are reported. They exhibit an ohmic behavior ascribed to p-type Si/PEDOT:PSS, whereas n-type Si/PEDOT:PSS displays a rectifying nature. Abstract : Si/PEDOT:PSS core/shell nanowire hetero-junctions with adjustable electrical characteristics are reported. They exhibit an ohmic behavior ascribed to p-type Si/PEDOT:PSS, whereas n-type Si/PEDOT:PSS displays a rectifying nature. A large interfacial area within the core/shell nanowire configuration is beneficial for charge transport, decreasing the resistance by 60% for p-type Si/PEDOT:PSS, and increasing the rectification ratio by 10 times for n-type Si/PEDOT:PSS as compared to the planar structure. By incorporating a perfluorinated ionomer into PEDOT:PSS, the reverse saturation current densities of n-type Si/PEDOT:PSS core/shell nanowire hetero-junctions are reduced by 2 to 4 orders of magnitude, and the rectification performances are enhanced.